1995
DOI: 10.1002/anie.199513661
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Total Synthesis of the Pharmacophore of the Anticancer Antibiotic CC‐1065 by Zirconocene‐ and Palladium‐Initiated Cyclizations

Abstract: Three steps suffice for constructing the pyrroloindolino framework of the pharmacophoric moiety 2 of the highly potent anticancer agent CC‐1065. The easily accessible bis(allylamino)bromobenzene 1 was transformed by successive cyclizations mediated by [Cp2Zr(Me)Cl] and by a Pd° complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Therefore the iodomethyl group in 11 was first transformed into an acetoxymethyl group. In earlier work on the synthesis of CC-1065 analogues [8] we had shown that, by means of 1,8-diazabicyclo [5.4.0]undec-7-ene, the iodomethyl group can easily be transformed into an exocyclic double bond, which on hydroboration becomes a hydroxymethyl group. Since the yields for this twostep transformation are not very high and a hydroboration is not possible due to the second double bond in 11, we tried to replace the iodo atom by a simple substitution with sodium acetate, cesium acetate, tetrabutylammonium acetate and several other nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the iodomethyl group in 11 was first transformed into an acetoxymethyl group. In earlier work on the synthesis of CC-1065 analogues [8] we had shown that, by means of 1,8-diazabicyclo [5.4.0]undec-7-ene, the iodomethyl group can easily be transformed into an exocyclic double bond, which on hydroboration becomes a hydroxymethyl group. Since the yields for this twostep transformation are not very high and a hydroboration is not possible due to the second double bond in 11, we tried to replace the iodo atom by a simple substitution with sodium acetate, cesium acetate, tetrabutylammonium acetate and several other nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
“…Benzenesulfonyl chloride (14.0 g, 79.4 mmol) was added to a solution of 18 (8.61 g, 39.7 mmol) in dry degassed pyridine (300 mL) and the mixture stirred for 3 h at 80 8C. After concentration to a volume of about 100 mL, ice-cold aqueous hydrochloric acid (500 mL, 5 % HCl) was added, the resulting black oil separated and C-6), 127.6 (C-2'', C-6''), 127.7 (C-2', C-6'), 128.1 (C-1), 128.5 (C-3'', C-5''), 128.9 (C-3', C-5'), 132.2, 132.4 (2 Â CHCH 2 ), 132.7 (C-4''), 133.1 (C-4'), 137.5 (C-1''), 140.7 (C-1', C-4), 158.1 (C-2); MS (70 eV): m/z (%) 437 (12) 5.83 ± 5.97 (mc,1 H,7.14 (s,1 H,7.48 ± 7.69 (m,6 H,7.72 ± 7.79 (m,2 H,Ph ± H),7.82 (d,J 8.0 Hz,2 H,Ph ± H); 13 C NMR (50 MHz, CDCl 3 ): d 7.643 (CH 2 ± I), 47.54 (C-3), 53.08 (N ± CH 2 ), 55.34 (O-CH 3 ), 55.37 (C-2), 98.63 (C-7), 105.6 (C-4), 119.1 (CHCH 2 ), 125.6 (C-5), 127.2 (C-2'', C-6''), 132.8 (CHCH 2 ),, 140.9 (C-1'), 142.1 (C-1''), 157.9 (C-6); MS (70 eV (C-7), 105.4 (C-4), 118.9 (CHCH 2 ), 125.0 (C-5), 127.3 (C-2'', C-6''), 127.8 (C-2', C-6'), 127.9 (C-3a), 128.5 (C-3'', C-5''), 129.3 (C-3', C-5'), 132.3 (C-4''), 133.0 (CHCH 2 ), 133.8 (C-4'), 136.8 (C-7a), 141.0 (C-1'), 142.8 (C-1''), 157.6 (C-6); MS (70 eV): m/z (%) 640 (8) -5), 127.0 (C-3a), 127.2 (C-2'', C-6''), 127.9 (C-2', C-6'), 128.5 (C-3'', C-5''), 129.4 (C-3', C-5'), 132.3 (C-4''), 132.7 (CHCH 2 ), 134.0 (C-4'), 136.7 (C-7a), 141.0 (C-1'), 142.8 (C-1''), 157.9 (C-6), 170.5 (CO); MS (70 eV): m/z (%) 682 (7) (1-RS)-6-Benzenesulfonyl-3-benzenesulfonyl-1-acetoxymethyl-8-methylidene-1,2,7,8-tetrahydro-6H-pyrrolo [3,2-e] 6 (C-1a), 127.3, 127.4 (C-2'', C-6'', C-2', C-6'), 128.5, 129.3 (C-3'', C-5'', C-3', C-5'), 130.6 (C-5a), 131.3 (C-8), 132.7, 133.7 (C-4'', C-4'), 136.5 (C-3a), 139.0 (C-1'), 140.8 (C-8a), 141.4 (C-1''), 151.7 (C-5) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble palladiums, generally palladium complexes such as [Pd(OAc) 2 ] and [Pd(PPh 3 ) 2 Cl 2 ], are the most efficient catalysts for the Heck reaction because of the stabilisation effect between the ligands and metal nanoparticles [4,5]. However, the main drawback of the homogenous catalysts is the difficulty of recycling and reusing the expensive metals and ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Heck reaction of aryl halide with olefins has recently been one of the most intensively studied transition-metal catalysed carbon-carbon bond-forming reactions and has been applied to many areas, including natural products [1,2] and fine chemicals [3]. Soluble palladiums, generally palladium complexes such as [Pd(OAc) 2 ] and [Pd(PPh 3 ) 2 Cl 2 ], are the most efficient catalysts for the Heck reaction because of the stabilisation effect between the ligands and metal nanoparticles [4,5].…”
Section: Introductionmentioning
confidence: 99%